Co-precipitation Synthesis by Malonate Route, Structural Characterization and Gas Sensing Properties of Zn-doped NiO. (2016) - Lontio Fomekong, R.; Lahem, D.; Debliquy, M.; Dupont, V.; Ngolui, J. Lambi; Delcorte, A.
Abstract: Zn-doped NiO powders have been prepared via pyrolysis at 500 °C of zinc-nickel malonate precursors prepared by co-precipitation using different molar ratios of Zn/Ni (0.01 - 0.04 and 0.1). Structural characterization of the powders was performed by X-ray powder Diffraction (XRD) and Time of Flight-Secondary Ion Mass Spectrometry (ToF-SIMS). The results confirm that a single phase of Ni1-x Znx O (x=0.01-0.04, 0.1) is formed. Electrical measurements reveal that its activation energy decreases with increasing amount of Zn. Gas-sensing measurements reveal that the optimal operating temperature is 300 °C and that the use of 2% Zn as a dopant improved the gas-sensing properties.